Nilai Waktu Uang dan Legitimasi dalam Perspektif Syariah - Lia Wardatul Umah; Risma Hermawati Apriliani; Naila Alya Fadila Hilman; Wafa Jannatul Ma'wa; Joni Joni (Journal of Islamic Economics and Finance, 2025)
Money has different functions and roles based on conventional and Islamic perspectives. The time value of money in Islam and conventional economics have different perceptions, which can lead to debate. In addition, the sharia legitimacy review of the time value of money in the conventional economic system raises a dividing line against the Islamic economic system. This research aims to examine the concept of the time value of money and its legitimizing role from a sharia perspective. The method used in this research is data analysis method using literature study with qualitative method. This research has implications for the theory and practice of Islamic finance.